1975
DOI: 10.1252/jcej.7.447
|View full text |Cite
|
Sign up to set email alerts
|

Deformations and Splittings of a Bubble in a Two-Dimensional Fluidized Bed

Abstract: The behavior of deformations and splittings of a single bubble was studied experimentally in a two-dimensional fluidized bed. It was found that small downward cusps were generated at the bubble surface near the stagnation point and that they grew and necessarily caused bubble deformations and, frequently, bubble splittings.The authors call these cusps "disturbances". The frequencies of disturbances and splittings were observed and the following results were found. 1) About 4~8 disturbances were generated per s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The frequency of bubble splitting does not depend upon bubble diameter but does depend upon particle diameter. Toei et al (1974a) data show thatf: is proportional to d;o.6 or possibly to d;'.'. Tone et al (1974) reported that bubble diameter decreases with increasing temperature.…”
Section: Description Of the Modelmentioning
confidence: 93%
See 2 more Smart Citations
“…The frequency of bubble splitting does not depend upon bubble diameter but does depend upon particle diameter. Toei et al (1974a) data show thatf: is proportional to d;o.6 or possibly to d;'.'. Tone et al (1974) reported that bubble diameter decreases with increasing temperature.…”
Section: Description Of the Modelmentioning
confidence: 93%
“…On the mechanism of bubble breakup, they found that it is initiated mostly from bubble roof, not from the wake as was expected by Davidson and Harrison (1963), and pointed out that the case should be treated as a Taylor instability problem. Toei et al (1974a) made a quantitative measurement of bubble splitting in a two-dimensional bed and found that the bubble splitting frequency does not depend on bubble diameter but does depend on the particle size. Their results are shown in Figures 1 and 2.…”
Section: Aicbe Journalmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the maximum stable diameter would depend on the terminal velocity of the bed material and therefore on the particle size, shape factor, and physical properties of the bed material. Data presented by Rowe and Partridge (1965) and by others Toei et al 1974) have raised questions about the validity of this criterion.…”
Section: 1;1 Bubble Growthmentioning
confidence: 98%
“…18) describes not only bubble growth by coalescence but also the splitting of bubbles (second term on the righthand side [49]). The crucial parameter here is the mean bubble lifetime λ:…”
Section: Bubble Developmentmentioning
confidence: 99%